Genotype-Specific Modulatory Effects of Select Spectral Bandwidths on the Nutritive and Phytochemical Composition of Microgreens - Kyriacou, Marios C.; El-Nakhel, Christophe; Pannico, Antonio; Graziani, Giulia; Soteriou, Georgios A.; Giordano, Maria; Zarrelli, Armando; Ritieni, Alberto; De Pascale, Stefania; Rouphael, Youssef (Frontiers in Plant Science, 2019)
Advanced analytical data on microgreens’ response to different light spectra constitutes a valuable resource for designing future crop-specific spectral management systems. The current study defined variation in productivity, nutritive and functional quality (mineral-carotenoid-polyphenolic profiles and antioxidant capacity) of novel microgreens (amaranth, cress, mizuna, purslane) in response to select spectral bandwidths (red, blue, blue-red) and appraised clustering patterns configured by the genotype-light-spectrum nexus. Growth parameters dependent on primary metabolism were most favoured by blue-red light’s efficiency in activating the photosynthetic apparatus. Nitrate accumulation was higher under monochromatic light owing to the dependency of nitrite reductase on the light-driven activity of PSI, most efficiently promoted by blue-red light. Although mineral composition was mostly genotype-dependent, monochromatic red and blue lights tended to increase K and Na and decrease Ca and Mg concentrations. Lutein, β-carotene and lipophilic antioxidant capacity were generally increased by blue-red light putatively due to the coupling of heightened photosynthetic activity to increased demand for protection against oxidative stress; the disparate response however of purslane highlights the importance of genotype specificity in these responses and calls for additional investigation. Analysis of polyphenols by Orbitrap LC-MS/MS revealed substantial genotypic differences. Most abundant phenolics were chlorogenic acid (x̄= 5503 µg g-1 dw), feruloylquinic acid (x̄= 974.1 µg g-1 dw) and caffeoylferuloyl tartaric acid (x̄= 5503 µg g-1 dw). Hydroxycinnamic acids accounted for 79.0% of the mean total phenolic content across species, flavonol glycosides for 20.7% and flavone glycosides for 0.3%. The general response across species was a decrease in individual polyphenolic constituents, particularly flavonol glycosides, and total polyphenols under blue-red light. The pronounced effectiveness of monochromatic blue light in eliciting synthesis of flavonoids could be linked to their capacity for absorbing shorter wavelengths thereby quenching generated photo-oxidation potential. The light-induced stimulation of the phenylpropanoid pathway by monochromatic blue light through epigenetic mechanisms or redox signalling in the photosynthetic apparatus warrants further investigation. The current work highlights how optimized genetic background combined with effective light management might facilitate the production of superior functional quality microgreens.